Personal Experience: A Most Vicious and Limited Circle!? On the Role of Entrepreneurial Experience for Firm Survival - Georg Metzger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
The analysis in this paper gives attention to effects on firm survival which come from entrepreneurial experience. It is likely that different kinds of experience result in different firm developments and therefore in different types of firm exit. Particular emphasis is placed upon the effects of failure experience. The results provide evidence that both the kind of experience and the type of exit matter. Negative experience, namely the experience of failure, is found to heighten the risk of failing again. This finding indicates that business failures are largely not exceptions, but rather a sign of the entrepreneurs' lack of ability.
Older version: http://hdl.handle.net/10419/24613
Keywords: G33; M13; L25; L26; 330; Entrepreneurial Experience; Business Failure; Firm Survival; Unternehmensgründung; Unternehmensentwicklung; Unternehmer; Berufserfahrung; Konkurs; Schätzung; Deutschland